PENGARUH RASIO LIKUIDITAS, RASIO SOLVABILITAS, DAN RASIO PROFITABILITAS TERHADAP EARNING PER SHARE ( Study Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2008-2011) - Eka Susilawati (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of this research was to determine whether Liquidity Ratios (Current Ratio), Solvency Ratio (Debt to Equity Ratio), and Profitability ratios (Return on Equity and Net Profit Margin) have an influence on Earning Per Share.The type of data in this study are secondary data, the sampling method is used purposive sampling and methods polled. The company used a sample of 26 of 136 companies listed on the Indonesia Stock Exchange during the period 2008-2011. This research is quantitative, and statistical testing using multiple linear regression test.The results of this study indicate that simultaneous four independent variables significantly influence the Earning Per Share. Partially shown that Current Ratio, Debt to Equity Ratio and Net Profit Margin has a positive and significant effect on Earning Per Share. While Return On Equity has a positive effect but not significant to Earning Per Share. Keywords: Current Ratio, Debt to Equity Ratio, Return On Equity, Net Profit Margin, Earning Per Share.